DOI: 10.14264/uql.2014.430
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese demonstratives: A spatially-based polysemy network

Abstract: For all human beings, a crucial function of language is to draw attention to things in the world. Like most languages, Vietnamese has its set of 'pointing words' that fulfil this function, including này 'this', đây 'this/here ' and đấy, đó, kia 'that/there', ấy 'that', and nọ 'that'. Though the meaning of these seven words has expanded and changed over time, all of them originally served to orient the hearer's attention to something proximal or distal to the speaker's location. These words are termed demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 65 publications
(156 reference statements)
1
7
0
Order By: Relevance
“…A completely contradictory pattern of demonstrative use could be recognized in Vietnamese essays when proximal demonstratives đây(này) tended to mark topic continuity and distal demonstratives đấy(đó), kia, ấy tended to signal topic discontinuity, which is similar to what was suggested by Bui (2014). She examined all instances of anaphoric demonstratives from various written discourse materials and concluded that while proximal demonstrative này expressed more important topics which were likely to be discussed again in the following discourse, distal demonstrative ấy indicated less important topics which were not likely to appear again.…”
Section: Different Uses In Topic Continuity/discontinuitysupporting
confidence: 56%
See 4 more Smart Citations
“…A completely contradictory pattern of demonstrative use could be recognized in Vietnamese essays when proximal demonstratives đây(này) tended to mark topic continuity and distal demonstratives đấy(đó), kia, ấy tended to signal topic discontinuity, which is similar to what was suggested by Bui (2014). She examined all instances of anaphoric demonstratives from various written discourse materials and concluded that while proximal demonstrative này expressed more important topics which were likely to be discussed again in the following discourse, distal demonstrative ấy indicated less important topics which were not likely to appear again.…”
Section: Different Uses In Topic Continuity/discontinuitysupporting
confidence: 56%
“…He suggested classifying Vietnamese demonstratives into three categories in accordance with their degree of distance: proximal đây(này), medial đấy(đó), ấy and distal kia; and implied that this distinction also had some relevance with the demonstratives' morphological features. However, this approach was revisited and refuted by Bui (2014) with a more comprehensive analysis of examples from various sources of written discourse (journals, poetry, conversations recorded in books). She argued that it was not appropriate to use the morphological approach to distinguish demonstratives, and there was no significant difference between the medial đấy(đó), ấy and distal demonstratives kia as Nguyen (1992) had proposed.…”
Section: Studies Of Vietnamese Demonstrativesmentioning
confidence: 99%
See 3 more Smart Citations